Responses of Microbial Community Composition to Temperature Gradient and Carbon Steel Corrosion in Production Water of Petroleum Reservoir - Li, Xiao-Xiao; Yang, Tao; Mbadinga, Serge M.; Liu, Jin-Feng; Yang, Shi-Zhong; Gu, Ji-Dong; Mu, Bo-Zhong (Frontiers in Microbiology, 2017)
Oil reservoir production systems are usually associated with a temperature gradient and oil production facilities frequently suffer from pipeline corrosion failures. Both bacteria and archaea potentially contribute to biocorrosion of the oil production equipment. Here the response of microbial populations from the petroleum reservoir to temperature gradient and corrosion of carbon steel coupons were investigated under laboratory condition. Carbon steel coupons were exposed to production water from a depth of 1809 m of Jiangsu petroleum reservoir (China) and incubated for periods of 160 and 300 days. The incubation temperatures were set at 37°C, 55°C and 65°C to monitoring mesophilic, thermophilic and hyperthermophilic microorganisms associated with anaerobic carbon steel corrosion. The results showed that corrosion rate at 55°C (0.162 ± 0.013 mm year-1) and 37°C (0.138 ± 0.008 mm year-1) were higher than that at 65°C (0.105 ± 0.007 mm year-1), and a dense biofilm was observed on the surface of coupons under all biotic incubations. The microbial community analysis suggests a high frequency of bacterial taxa associated with families Porphyromonadaceae, Enterobacteriaceae and Spirochaetaceae at all three temperatures. While the majority of known sulfate-reducing bacteria, in particular Desulfotignum, Desulfobulbus and Desulfovibrio spp., were predominantly observed at 37°C; Desulfotomaculum spp., Thermotoga spp. and Thermanaeromonas spp. as well as archaeal members closely related to Thermococcus and Archaeoglobus spp. were substantially enriched at 65°C. Hydrogenotrophic methanogens of the family Methanobacteriaceae were dominant at both 37°C and 55°C; acetoclastic Methanosaeta spp. and methyltrophic Methaolobus spp. were enriched at 37°C. These observations shows that temperature changes significantly alter the microbial community structure in production fluids and also affected the biocorrosion of carbon steel under anaerobic conditions.